The ability of pentose pathways to form all essential metabolites provides clues to the origins of metabolism. - Steffen N Lindner; Markus Ralser (PLoS Biology)
The structure of the early metabolic network is unknown. Here, we report that when considered together, pentose utilization pathways form all life-essential precursors. We speculate that the chemistry preserved in pentose metabolism could therefore have been a central structural element in early metabolism.